Patient-individual tapering of DMARDs in rheumatoid arthritis patients in a real-world setting - Birkner, Benjamin; Rech, Jürgen; Edelmann, Edmund; Verheyen, Frank; Schett, Georg; Stargardt, Tom (Rheumatology, 2022)
Objective We aim to provide real-world evidence on the effectiveness of patient-individual tapering of DMARDs for patients with RA in daily clinical practice using medical records and claims data. Methods We utilize data obtained through a controlled prospective cohort study in Germany conducted from July 2018 to March 2021. Participants consist of RA patients in sustained remission (>6 months) who were eligible for tapering at enrolment. Patients treated with individual tapering based on shared decision making (n = 200) are compared with patients without any dose reduction (n = 237). The risk of loss of remission and the risk of flare is assessed with risk-adjusted Kaplan-Meier estimators and Cox regressions. We evaluate differences in costs 1 year before and after baseline based on claims data for the subgroup of patients insured at one major sickness fund in Germany (n = 76). Results The risk of flare (hazard ratio 0.88, 95% CI 0.59, 1.30) or loss of remission (hazard ratio 1.04, 95% CI 0.73, 1.49) was not statistically different between the individual tapering group and the continuation group. Minor increases of disease activity and decreases of quality of life were observed 12 months after baseline, again with no statistically significant difference. Drug costs decreased by 1017euro in the individual tapering group while they increased by 1151euro in the continuation group (P < 0.01). Conclusion Individual tapering of DMARDs does not increase the average risk of experiencing flares or loss of remission. Encouraging rheumatologists and patients to apply tapering in shared decision making may be a feasible approach to allow individualization of treatment in RA.
CRIS-Team WoS Importer:2022-09-16